An Islamic Wholly Understanding of Attention Deficit/Hyperactivity Disorder (ADHD) - Binti Ibrahim, Nur Aifiah (Insititut Agama Islam Negeri (IAIN) Curup, 2024)
Attention Deficit/Hyperactivity Disorder (ADHD) encompasses neurobehavioural changes that may affect the child's development, including inattentiveness, hyperactivity, or impulsivity. Before this, without even knowing, they were troublemakers as they acted in different possible ways to get attention. In the latest update, both Attention Deficit Disorder and ADHD are becoming a proposed health condition in the psychiatric field. Early detection suggested that lack of concentration and focus, memory deficit, and being disorganised are signs and symptoms of ADHD. It does affect daily routines, job employment, and social interactions as ADHD becomes more severe than ever. The prevalence of ADHD is becoming more profound in local community settings and global stage population. Therefore, in Islam, shaping and nurturing them to be who they want to be and life is what you make of it. Thus, this review focuses on brief Islamic perspectives of the problem, definition and diagnosis of ADHD, and treatment options and management available for ADHD.